2022
DOI: 10.2337/dc22-0105
|View full text |Cite
|
Sign up to set email alerts
|

A Diabetes Genetic Risk Score Is Associated With All-Cause Dementia and Clinically Diagnosed Vascular Dementia in the Million Veteran Program

Abstract: OBJECTIVE Diabetes and dementia are diseases of high health care burden worldwide, and studies have shown that diabetes is associated with an increased relative risk of dementia. We set out to examine whether type 2 diabetes–associated genetic variants were associated with dementia and whether they differed by race/ethnicity or clinical dementia diagnosis. RESEARCH DESIGN AND METHODS We evaluated associations of two type 2 di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Our study confirms what a number of epidemiological studies have shown previously, which is that type 2 diabetes is associated with an increased risk of dementia, in particular vascular dementia. 1 Similar to a study published very recently (in November 2022), 7 we also identify a link between PRS for type 2 diabetes and dementia (all-cause dementia and vascular dementia), which other previous studies have not been able to do. 5 , 6 One reason for this could be that we have well validated data on dementia diagnoses, while other genetic studies previously have used other ways of defining dementia or cognitive impairment (e.g.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our study confirms what a number of epidemiological studies have shown previously, which is that type 2 diabetes is associated with an increased risk of dementia, in particular vascular dementia. 1 Similar to a study published very recently (in November 2022), 7 we also identify a link between PRS for type 2 diabetes and dementia (all-cause dementia and vascular dementia), which other previous studies have not been able to do. 5 , 6 One reason for this could be that we have well validated data on dementia diagnoses, while other genetic studies previously have used other ways of defining dementia or cognitive impairment (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…These are very similar findings to a recent study with similar study design as ours. 7 This other study had a larger study sample size than ours, but did not analyse the dementia diagnoses longitudinally using time to event as outcome, and did not have validated dementia diagnoses. The findings in our two studies are in contrast to a meta-analysis that reported that APOE ε4 carriers are more vulnerable to diabetes-associated dementia.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…[1113] Our previous work in the Million Veteran Program (MVP) demonstrated that a genetic risk score (GRS) for type 2 diabetes (T2D) is associated with all-cause dementia and clinically diagnosed vascular dementia (VaD), and less strongly with clinically diagnosed AD. [14] Like prior observational studies, however, our study strictly assessed an association between T2D and all-cause, VaD, and/or AD without evaluating a causal relationship.…”
Section: Introductionmentioning
confidence: 99%